Influence of nutritional status on clinical outcomes in hospitalised children - Jimena Pérez Moreno; Sara de la Mata Navazo; Estíbaliz López-Herce Arteta; Mar Tolín Hernani; Felipe González Martínez; M. Isabel González Sánchez; Rosa Rodríguez Fernández (Elsevier, 2019)
Introduction: Paediatric malnutrition during hospital admission is a prevalent comorbidity, which is estimated around 31.4% in our environment, and could influence the clinical outcomes of paediatric patients. Objective: The aim of this study was to describe the malnutrition risk in hospitalised children using STAMP (Screening Tool for the Assessment of Malnutrition in Paediatrics), and to study its relationship with clinical outcomes. Methods: A single-centre, analytical and prospective study was conducted on children aged 1 month to 15 years hospitalised in a tertiary hospital between October and December 2017. An analysis was made of the clinical data and anthropometric measurements (weight, height, Waterlow weight classification). Patients were classified according to STAMP, which is a validated screening tool used to classify the risk of paediatric malnutrition during hospital admission. Multivariate statistical analysis was used to identify predictive variables of illness severity. Results: An analysis was made on a total of 200 patients (55% male), with a median age of 15.8 months (IQR 2.5-42.8), and a median length of stay of 3 days (IQR 1-18 days). Almost half (48.3%) of them had high risk of malnutrition at admission (STAMP ≥4), and 48.2% showed medium risk (STAMP 2-3). A higher STAMP score was associated with longer length of hospital stay (P < .01) and greater severity (P < .01). Multivariable analysis showed that STAMP could be a predictor of illness severity (OR 1.48, 95% CI: 1.18-1.86, P < .01). Conclusions: Nearly 50% of hospitalised children have a high risk of malnutrition at admission according to the STAMP screening tool. Risk of malnutrition at admission measured according to STAMP nutritional screening was associated with a longer length of stay and greater severity of illness. It is important to evaluate the risk of malnutrition as this could be related to illness severity. Resumen: Introducción: La desnutrición en el paciente pediátrico hospitalizado es una comorbilidad prevalente que puede influir en la evolución clínica y se estima en un 31,4% en nuestro medio. Objetivo: Nuestro objetivo fue describir el riesgo de desnutrición de los pacientes que ingresan en nuestro centro, mediante la herramienta Screening Tool for the Assessment of Malnutrition in Paediatrics (STAMP), así como analizar su asociación con la evolución del ingreso hospitalario. Métodos: Se realizó un estudio prospectivo, unicéntrico y analítico desde octubre hasta diciembre de 2017 en pacientes hospitalizados, de edades entre 1 mes y 15 años. Se recogieron variables clínicas y datos antropométricos (peso, talla, peso según Waterlow al ingreso (T0), a las 48 h (T1) y al alta (T2). Se construyeron modelos multivariantes para identificar variables predictoras de gravedad. Resultados: Analizamos a 200 pacientes (55% varones) con una mediana de edad de 15,8 meses (RIQ 2,5-42,8) y una estancia media de 3 días (RIQ 1-18 días). El 48,3% presentaba alto riesgo de desnutrición en T0 (STAMP ≥ 4) y un 48,2% riesgo moderado (STAMP = 2-3). En el análisis bivariante, una mayor puntuación de STAMP se asoció a mayor estancia media (p < 0,01) y a mayor gravedad (p < 0,01). En el análisis multivariante, el STAMP en T0 fue predictor de gravedad (OR 1,48; IC 95%: 1,18-1,86; p < 0,01). Conclusiones: Casi el 50% de los pacientes ingresados tenían un elevado riesgo de desnutrición durante el ingreso. El riesgo de desnutrición al ingreso medido según el cribado nutricional STAMP se asoció con una mayor estancia media y mayor gravedad. Es importante evaluar el riesgo de desnutrición al ingreso dada su influencia en la evolución de la enfermedad.